Оn the question of interference of «language policy», «language planning» and «language ideology» concepts - Heidemari, S.; Amanbayeva, G.Yu.; Shunkeyeva, S.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The key concepts of modern sociolinguistics: «language policy», «language planning» and «language ideology » can be defined variously and that demonstrates the diversity of scientists’ views on their content. In this article, the authors have attempted to analyze existing, often opposing, approaches – how to define the content of these concepts, how to demonstrate the heterogeneity of their terminological field, how to identify and to establish correlations of the analyzed concepts. The article presents an analysis of the above-mentioned concepts of both domestic and foreign linguistic scientists who consider these concepts by the type of relationship between them. As a result, the authors have come to the conclusion that «language policy», «language planning» and «language ideology» are interdependent. The authors used such general scientific methods of research as analysis and synthesis, comparison and generalization, and systems-based approach.
«Тілдік саясат», «тілдік жоспарлау», «тілдік идеология» түсініктердің өзара шарттылық мəселесі
К вопросу взаимообусловленности понятий «языковая политика», «языковое планирование», «языковая идеология»
Keywords: sociolinguistics; language policy; language ideology; language planning; linguistic situation; language status; language management; language landscape